Entre o On e o Off: personalidades que se criam, a interação entre pessoas nas redes sociais - Picchia, Pedro da Cunha Del (2013)
This research aims to further the understanding of the relationship between on and offline personalities in digital social networks. It focuses on the behavior of users from the online social network Twitter. This network was specifically chosen because it provides not only comunicational relevance but also three distinguishing characteristics. The first is an unique freedom to create an avatar. The second is a high speed in the exchange of messages, which is significant because of the premisse that relevant users are those that interact frequently with the network. And, finally, an also unique following/follower structure, which promotes the emergence of leaders and subgroups. The theoretical framework is based on the concepts of digital-glocal environments proposed by Trivinho Dal Bello (2009), digital avatars as defined by Cavalheiro in his master's dissertation (2008), Lazarsfeld's (1995) theory of two-step-flow of information and also in a context analysis of the freudian theory presented in Mass Psychology (1921). The hypothesis is that the creation of an avatar personality follows influence and leadership patterns. The methodology is based on an analysis of widely shared posts from several users and interviews with three study participants who have popular avatars in Twitter